1996
DOI: 10.1159/000177147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Triiodothyronine on the Survival of High-Risk Patients Undergoing Open Heart Surgery

Abstract: Experimental and clinical studies have shown the beneficial effects of triiodothyronine (T3) following myocardial revascularization on cardiopulmonary bypass (CPB). In this study, open-label T3 was administered to 68 high-risk patients undergoing open heart surgery. The New Jersey Risk Assessment was used to calculate the preoperative estimated surgical mortality. A loading dose of T3 was administered: (a) at release of the aortic cross-clamp, (b) whenever the patient became CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 30 publications
(33 reference statements)
1
18
0
2
Order By: Relevance
“…The longer aortic clamping time and lower ejection fraction in the T group, although not statistically significant (P = 0.083 and 0.099, respectively), raise the possibility that the patients randomly allocated to this group had more complex cardiopathies and that their surgical procedure was more complicated. Other studies demonstrated that T 3 replacement reduced clinical endpoints postoperatively, such as the need for pacemaker and mechanical assistance, use of vasoactive drugs, need for intensive care, or prevalence of atrial fibrillation (8,10,12,15,18), and some studies have even suggested decreased mortality (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer aortic clamping time and lower ejection fraction in the T group, although not statistically significant (P = 0.083 and 0.099, respectively), raise the possibility that the patients randomly allocated to this group had more complex cardiopathies and that their surgical procedure was more complicated. Other studies demonstrated that T 3 replacement reduced clinical endpoints postoperatively, such as the need for pacemaker and mechanical assistance, use of vasoactive drugs, need for intensive care, or prevalence of atrial fibrillation (8,10,12,15,18), and some studies have even suggested decreased mortality (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the intravenous administration of T 3 to adults (8)(9)(10)(11)(12)(13)(14) and, more recently, to children (15)(16)(17), during the cardiac surgery postoperative period. The results concerning clinical benefits, actual hemodynamic effects and need for inotropic drugs have been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism hypothesized to explain the low T3 state involves the regulation of specific 5 -monodeiodinases converting T4 to T3 which is considered to be the thyroid hormone in the biologically active form (Salter et al 1992). Data from the literature on thyroid hormone metabolism during and after cardiac surgery are mainly derived from studies based on patients undergoing coronary artery bypass during operations carried out with the extra-corporeal circulation procedure (Klemperer et al 1995, Novitzky et al 1996. The original approach introduced in the present study consisted of the evaluation either of patients undergoing cardiac surgery carried out using extra-corporeal circulation or patients Baseline 1·33 0·09 104·4 1·9 3·98 0·21 20·9 2·3 2·21 1·0 6·34 0·3 Pre-anesthesia 1·27 0·09 104·7 8·3 3·59 0·14 17·5 0·7 2·02 0·8 5·96 0·2 Post-sternotomy 1·22 0·09 104·9 5·9 4·10 0·62 16·8 4·7 2·30 1·1 5·57 0·2 Post-surgery 0·95 0·04 91·7 4·9 3·48 0·22 20·7 1·9 1·85 0·9 4·27 0·3 2 h 0·96 0·10 92·5 6·0 3·31 0·11 19·5 1·4 1·30 0·6 4·58 0·3 OPCAB…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the data reported in the literature on this topic are quite discordant, the rapid and significant decrease in tri-iodothyronine (T3) levels is a confirmed finding (Teiger et al 1993, Klemperer et al 1995, Murzi et al 1995, Novitzky et al 1996. Investigators have defined this condition as 'low T3 syndrome' (Broderick & Wechsler 1997) and have described it as a direct consequence of impairment in the enzymatic mechanism converting thyroxine (T4) to T3 (Holland et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown the effect of thyroid hormones on morbidity and mortality from heart failure 2-3 , systemic arterial hypertension 4 , atherosclerosis 5 , dyslipidemia 6 and cardiopulmonary surgeries [7][8] . Serum thyroid hormone levels have been described in several systemic nonthyroidal illnesses, among them acute heart diseases.…”
mentioning
confidence: 99%